Atlas of Medical Renal Pathology - Bonsib, Stephen M. (Atlas of Anatomic Pathology,, 2013)
The kidney is an organ with complex organogenesis susceptible to numerous misadventures in development and is exposed to a diverse array of insults of hematogenous and lower urinary tract origin. This Atlas of Medical Renal Pathology provides an overview of the development, macroscopic and microscopic features of the normal kidney. This is followed by a comprehensive survey of developmental and cystic kidney diseases, vascular diseases and tubulointerstitial diseases. An emphasis is placed on gross diagnostic findings with detailed histological correlates. In addition, the histological, immunofluorescent, immunohistochemical and ultrastructural features of the major glomerular diseases and renal transplantation pathology are presented. This compendium of non-neoplastic kidney diseases illustrates the vast majority diseases you are likely to encounter in surgical and autopsy pathology.